Penyuluhan dan Pendampingan Pengelolaan Sampah di Kampus PPNP: Upaya Pengabdian kepada Masyarakat - Veronika Sriwulantari; Reni Ekawaty; Harmailis Harmailis; Edi Joniarta (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2025)
Waste management in Indonesia faces severe challenges, evidenced by landfill fires and the functional collapse of the Payakumbuh Regional Landfill, which led to the lowest waste handling coverage in Lima Puluh Kota Regency, West Sumatra (6.23%). This occurs despite the high recycling potential of organic waste (47% of total waste composition). Low sorting awareness and limited infrastructure are primary constraints. Politeknik Pertanian Negeri Payakumbuh (PPNP) holds a strategic role as an agent of change, yet its internal campus waste management system remains conventional. This community engagement project aimed to enhance waste management knowledge and skills among PPNP cleaning staff and students. The methodology involved four stages: identifying specific campus waste issues, designing educational materials on waste segregation and organic waste processing (composting, BSF maggot bioconversion), 3R principles, and agricultural utilization; conducting face-to-face training and ongoing mentoring; and evaluating impacts. Results showed high participation from 15 cleaning staff and 10 students. Cleaning staff's understanding improved significantly from 55% to 87%. Mentoring successfully encouraged waste segregation and organic waste processing practices, indicating a reduction in mixed waste disposed to the landfill. The program effectively increased individual capacity and fostered behavioral changes towards more independent and sustainable campus waste management. PPNP has the potential to serve as a model for waste management extension.